Documentary Film Procdution for Lettering Time Community to Support Brand Awareness - Reyhan Nazarindra; Sri Wulandari, S.Sn., M.A.; Aileena Solicitor.C.R.E.C, S.T,.M.Ds. (Texture : Art And Culture Journal, 2025)
The Lettering Time community, established in Surabaya in 2023 under the auspices of the Better Youth Foundation, functions as a platform for young people to develop skills in lettering and calligraphy. More than just an artistic outlet, the community serves as a vital channel for communication and self-expression, offering a safe space for youth to relieve stress and express their thoughts, particularly while navigating the challenges of the quarter-life crisis. The core mission of Lettering Time is to spread goodness and inspiration through the medium of handmade letters. To achieve this mission, the community holds regular "Lettering Time" activities, gathering members to learn techniques, share knowledge, and engage in discussions. Although these activities are archived on the official Instagram account to attract public participation, the community consistently faces a significant challenge: fluctuating weekly attendance levels. Consequently, a more effective and engaging media strategy is necessary to substantially enhance the community's brand awareness beyond simple photo documentation. This project proposes the implementation of a documentary film as the solution. This film is expected to serve as a powerful medium for conveying the community's unique, inspiring story and its positive impact on youth. The goal is to build a distinctive and credible public image, ensuring that the community is widely recognized and successful in attracting broader youth engagement. The documentary will be produced using Adobe Premiere Pro and distributed via the YouTube platform